EFFECTIVENESS OF ANTIHYPERTENSIVE THERAPY IN PREGNANT WOMEN - Kamolova Diyora Djamshedovna, Khusainova Munira Alisherovna , Gafforov Xudoyor Xudoyberdiyevich, Toirov Doston Rustamovich (Journals Park Publishing, 2023)
Arterial hypertension in pregnant women - The criteria for diagnosing arterial hypertension in pregnant women are an increase in systolic blood pressure ≥140 mm Hg or diastolic blood pressure≥90 mm Hg. Elevated blood pressure should be confirmed with two measurements using a mercury sphygmomanometer (V tone is used to register diastolic blood pressure) in a sitting position or an aneroid device. It is possible to measure blood pressure lying on the left side. Only validated tonometers and devices for outpatient monitoring should be used. The results of outpatient blood pressure monitoring make it possible to predict outcomes more accurately than the office measurement of blood pressure. Gestational hypertension, accompanied and not accompanied by proteinuria, is an increase in blood pressure associated with pregnancy itself. Complicates the course of pregnancy in 6-7% of cases. Preeclampsia is a pregnancy-specific syndrome that develops at 21 weeks gestation. and more and is characterized by de novo arterial hypertension in combination with proteinuria ≥ 0.3 g/day. Preeclampsia is a systemic disease that causes changes in the body of both mother and fetus. Edema is no longer considered a diagnostic criterion today, since their frequency in the normal course of pregnancy reaches 60%. In general, preeclampsia complicates the course of pregnancy in 5-7% of cases, but its frequency increases to 25% in women with arterial hypertension before pregnancy. Preeclampsia is more common during the first pregnancy, multiple pregnancies, bladder drift and diabetes mellitus. Preeclampsia is gestational hypertension, which is accompanied by proteinuria (≥ 0.3 g / day in daily urine or ≥30 mg /mmol of creatinine in a single portion of urine). Gestational hypertension develops from 21 weeks of gestation and in most cases passes within 42 days after delivery. It leads to deterioration of organ perfusion. It is combined with placental insufficiency, which often leads to a deterioration in fetal growth. Additionally, preeclampsia is one of the most common causes of prematurity. Its share in the structure of the causes of the birth of children with very low body weight (less than 1500 g) is 25%, and in the structure of the causes of premature birth – 50%. Severe preeclampsia is the cause of intracranial hemorrhages and acute renal failure, which together account for up to 90% of the causes of all deaths in pregnancy with preeclampsia.
Keywords: Hypertension in pregnant women, gestational hypertension, morphofunctional parameters of the heart, central α2-agonists, β-blockers, calcium antagonists